INVESTIGATION OF MATERIAL RESISTANCE TO PLASTIC DEFORMATION AT PROCESSING METALS BY PRESSURE WITH IMPOSING ULTRASONIC OSCILLATIONS - V. V. Klubovich; V. N. Sakevich; I. A. Tovpenets (Наука и техника)
The paper contains substantiation for application of experimental technique in order to investigate material resistance to plastic deformation at processing metals by pressure with imposing ultrasonic oscillations while proceeding from laws of similarity. It is shown that at modeling any metal processing by pressure with imposing ultrasonic oscillations it is possible to consider that actual elastic and plastic metal properties remain constant during processing under ultrasound action. The second aspect that requires a special attention at modeling is pulse or vibration-shock deformation at processing metals by pressure with imposing ultrasonic oscillations.